Association of hepatitis B virus DNA levels with efficacy and safety and the impact of antiviral therapy on prognosis in liver cancer patients receiving immune checkpoint inhibitors therapy: a systematic review and meta-analysis - Hongxia Cui; Su Li; Wu Lv; Jing Xiang (Frontiers in Microbiology)
BackgroundThe current evidence regarding the relationship between baseline hepatitis B virus (HBV) DNA levels and survival outcomes in liver cancer patients receiving immune checkpoint inhibitors (ICIs) remains inconsistent. Therefore, this review was intended to explore the impact of the baseline HBV-DNA level on the efficacy and safety of ICIs in patients with liver cancer.MethodsRelevant studies were identified through a comprehensive search in PubMed, EMBASE, Cochrane Library, and Web of Science up to August 1, 2024. The outcomes were hazard ratios (HRs) for overall survival (OS) and progression-free survival (PFS), as well as odds ratios (ORs) for objective response rate (ORR), disease control rate (DCR) and HBV reactivation (HBVr). Subgroup analysis, publication bias, and sensitivity analysis were conducted with STATA 14.0.ResultsThis meta-analysis comprised 17 articles involving a total of 2,130 patients. The pooled results demonstrated that high HBV DNA was associated with a worse OS (HR = 1.48 95% CI 1.11–1.96). Further subgroup analysis showed that there was no difference in OS between the high HBV DNA group and low HBV DNA group when all patients received antiviral treatment. No associations between baseline HBV DNA and PFS (HR = 1.08, 95% CI 0.90–1.29), ORR (OR = 0.91, 95% CI 0.65–1.28), or DCR (OR = 0.83, 95% CI 0.58–1.20) were observed. The risk of HBVr in the high HBV DNA group was lower than that in the low HBV DNA group (OR = 0.30, 95% CI 0.15–0.58), especially among patients who received antiviral therapy (OR = 0.42, 95% CI 0.18–0.98).ConclusionHigh HBV DNA was associated with worse OS, but not with PFS, ORR, or DCR in liver cancer patients receiving ICIs. When patients were simultaneously treated with antiviral treatment, elevated HBV DNA level had no unfavorable impact on the efficacy of ICIs. Furthermore, the risk of HBVr in the high HBV-DNA group was lower than that in the low HBV DNA group. More prospective studies with larger sample sizes are essential to confirm the results.